If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 = 3(y + -5) + -5y Reorder the terms: -17 = 3(-5 + y) + -5y -17 = (-5 * 3 + y * 3) + -5y -17 = (-15 + 3y) + -5y Combine like terms: 3y + -5y = -2y -17 = -15 + -2y Solving -17 = -15 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -17 + 2y = -15 + -2y + 2y Combine like terms: -2y + 2y = 0 -17 + 2y = -15 + 0 -17 + 2y = -15 Add '17' to each side of the equation. -17 + 17 + 2y = -15 + 17 Combine like terms: -17 + 17 = 0 0 + 2y = -15 + 17 2y = -15 + 17 Combine like terms: -15 + 17 = 2 2y = 2 Divide each side by '2'. y = 1 Simplifying y = 1
| -16h^3+80h^2y-100hy^2= | | 19-4*x=11+2*x | | 36v^2-84vg+49g^2= | | 15-6*x=11+4*x | | 21=2(w+3)+3w | | 10a^3+7a^2+1a=0 | | 17(t-5)+4t=7(3t+4)-10 | | 2(x-4)-6x=32 | | (2m-15p)=(3mp+10) | | (2m-15)=(3mp+10) | | (2m-15)-(3mp+10)=0 | | 5y^2-4y^3-7y^2+6Y^3= | | 10x-5x-3x=6 | | 15y^4-25y^3= | | -2y+8=9y+4 | | 20x^2y-4xy^2= | | 6+4(s-5t)= | | 2x^2-60x-385=415 | | 2a^2+11ab+15b^2=0 | | 18y^4-9y^3= | | 48y^2-8y^3= | | 5(x-3)=0 | | b^2-4= | | 8a^2-10ab-3b^2= | | -6(t-2)-(t+5)=6 | | -16x^2+16x+5= | | -6(t-9)-(t+3)=10 | | -20z^2+20z+5= | | -3(3n+2)=6 | | 7x-2=3x+6 | | 20m^2+21m+4= | | 6-2x=2x-6 |